PENGARUH PEMBERIAN LIMBAH PADAT (SLUDGE) KELAPA SAWIT DAN PUPUK ORGANIK CAIR TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN JAGUNG MANIS (Zea Mays Saccharata) - Darmawati J.S; Nursamsi ,; Abdul Rasid Siregar (AGRIUM: Jurnal Ilmu Pertanian, 2014)
The aims of this study was to investigate the effect of solid waste (sludge), oil palm and organic fertilizer on the growth and yield of sweet corn . The experiment was a factorial randomized block design with three replications, consisting of two factors, the first factor studied : solid waste (sludge), palm oil (S), with the solid waste ( sludge ), oil palm (S0), 3 to 4 kg/plot (S1), 6.8 kg/plot (S2), the second factor is a liquid organic fertilizer (D), without fertilizer (D0), 1.5 ml/l of water (D1), 3 ml/l of water (D2) and 4.5 ml/l of water (D3). The parameters measured were plant height (cm), leaf (leaves), leaf width (cm), stem diameter (cm), ear length (g), ear weight sampling (g), ear weight plant (g), ear weight perplot (kg). Giving solid waste (sludge), oil palm showed a noticeable effect on ear length parameters per sample, ear diameter, ear weight and ear weight per plant per plot. Liquid organic fertilizer showed a noticeable effect on the number of leaves per sample ear length, ear diamete , ear weight and ear weight per plant per plot. The combination of solid waste (sludge) palm oil showed a significant influence on plant height, leaf number, stem diameter, ear length per sample, the diameter of the ear, ear weight and ear weight per plant per plot. Keywords : palm oil, organic fertilizer, sweet organic